The Importance of Waqf in islamic economy development / Arief Hady Zaini Amri - Zaini Amri, Arief Hady (2019)
There is an opinion among Western scholars that the institution of waqf could not any longer perform its economic role in the present times. Instead of being a vital institution as it truly played in the pre-modern era, waqf nowadays seems to be an impediment to the development in Muslim countries. This paper, therefore, is meant to refute such an opinion and attempts to point out the importance of waqf in Islamic economic development for Muslim society in the context of the present economy. This research being conducted by using a library research method to concluded the finding of this research. This research included the concept of waqf, comparison between waqf, zakat, and sadaqah. In the last part, the paper also brings about the finding which is the importance of waqf in Islamic economy development which has played a big role in Muslim society.